Spermatozoa Quality of Pasundan Cattle Frozen Semen at Various Thawing Temperatures and Durations - Surjamah, Surjamah; Somanjaya, Rachmat; Widianingrum, Dini (Jurnal Sain Peternakan Indonesia, 2024)
Pasundan cattle are West Java's indigenous Genetic Resources, and the proper frozen semen thawing technique is necessary for successful artificial insemination (AI) to increase the cattle population. This study aimed to evaluate the quality of spermatozoa of Pasundan cattle frozen semen post-thawing at various temperatures and thawing duration. A total of 24 frozen semen samples were thawed with two treatment factors: temperature (27 and 37°C) and thawing duration (15, 20, 25, and 30 seconds). The observed variables included motility, viability, and plasma membrane integrity. Data were analyzed using the General Linear Model (GLM) for these variables, followed by the Tukey test for multiple comparisons. The results showed no interaction between temperature and thawing time on the observed variables. There was no significant difference (p>0.05) in sperm motility between treatments, with values ​​between 45.30±0.78 and 52.57±3.59%. Furthermore, the sperm viability rate was significantly different (p<0.05) due to temperature and thawing time. Sperm viability was higher in the 37°C thawing group for 15 seconds. In contrast to the integrity of the sperm plasma membrane, the 27°C temperature treatment group had a higher rate than the 37°C treatment group. It can be concluded that thawing frozen semen of Pasundan cattle at 27 or 37°C with a duration of 15-30 seconds produces normal spermatozoa quality, and a temperature of 37°C for 30 seconds is recommended for the thawing process. These findings contribute to optimizing thawing protocols in artificial insemination practices, enhancing the reproductive success of Pasundan cattle.